La directionnalité et la nature non-téléologique de l’évolution linguistique - Brian Lowrey (Anglophonia)
This paper deals with the nature of linguistic change, and, taking examples from the history of English, seeks to show that, contrary to what appears to be a widely held assumption, there is no reason to suppose that because one language undergoes a certain type of change, a similar change will necessarily take place in other, related languages. On the contrary, purely local factors may, and indeed often do decide which potential innovations will succeed, and which will fail. We look at two areas of English grammar in particular, the so-called ‘narrative perfect’ and infinitival complements of causative verbs, and compare the changes which have taken place within these fields in English to those which have occurred in French. The comparison shows not only that French and English have evolved in completely different directions, but also that assuming language change to be teleological in nature can lead to the wrong predictions being made as to which developments are likely to take place in the future